The influence of incident and reflected potential wave on the point vortex evolution near a solid surface - Kulik, K.N.; Tur, A.V.; Yanovsky, V.V. (Вопросы атомной науки и техники, 2007)
The influence of oscillation potential modes upon the point vortex movement near a solid wall is studied. The equations describing the point vortex movement in the given field of a potential wave in the presence of a solid wall are obtained. The character of the vortex movement is shown to change qualitatively under the influence of a potential wave. All the possible modes of vortex movement under the influence of a potential wave are analyzed. Вивчена дія потенційних мод коливань на рух точкового вихору поблизу твердої стінки. Отримані рівняння, які описують рух точкового вихора у заданому полі потенційної хвилі у наявності твердої стінки. Показано, що характер руху вихору під дією потенційної хвилі змінюється. Проаналізовані всі можливі режими руху вихору під дією потенційної хвилі. Изучено влияние потенциальных мод колебаний на движение точечного вихря вблизи твердой стенки. Получены уравнения, описывающие движение точечного вихря в заданном поле потенциальной волны при наличии твердой стенки. Показано, что характер движения вихря под влиянием потенциальной волны качественно меняется. Проанализированы все возможные режимы движения вихря под воздействием потенциальной волны.